Indicators Of Physical Development Of Preschool Children - Usmanov Zoxidjon; Boyjonova Odinahon (Genius Journals, 2022)
The article presents the results of a survey conducted by questionnaire to study the role of physical education in the family agenda, children's physical fitness and physical activity
Keywords: Physical development; functional, exercise; training; posture